Professor of mathematics Vytautas Paulauskas (1910–1991) 100 years - Jasiūnas, Henrikas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2010)
V. Paulauskas life review. Scientific work. Bibliographical listing.
Keywords: special functions; differencial equations; equations of mathematical physics; interpolation and approximation theory